The rise of (sub)nations? Sub-national human development, climate targets, and carbon dioxide emissions in 163 countries. (October 2020) - Pascale, Andrew; Chakravarty, Shoibal; Lant, Paul; Smart, Simon; Greig, Chris
Abstract: Is the notion of universal human development compatible with a world that is warmed less than 2°C? We estimate country-level quintile distributions of human development and consumption carbon dioxide (CO2 ) emissions for over 95% of the world's population. We find that <0.2% of the global population simultaneously experience high human development and meet long-term climate targets. Only one nation, Sri Lanka, contributed quintile populations (second and third) which exhibited both High Human Development Index (HDI) scores and long-term average per capita CO2 emissions consistent with global climate targets. Sub-national framing exposes within-country inequality, which continues to grow in China and India, and shows us that very high human development populations live in 89 nations, comprise 1.59 billion people, and are responsible for 53% of global emissions. Indeed, the wealthiest quintile in China (totaling 86% of the population of the USA in 2014) has very high human development and has per capita emissions similar to the fourth richest quintile of the USA.